Psychological characteristics of a tourist as predictors of expenditures: An analytical review and proposal of the predictive model - Robert Štefko; Jozef Džuka; Eva Litavcová; Darina Ňakatova; Martin Lačný (Contemporary Economics, 2020)
Tourism plays an important role in the economies of countries, which is evidenced by macroeconomic studies. However, analyses highlighted the need to do research on tourist expenditure and to identify factors at the microeconomic level. The article presents an overview of the extensively investigated and validated predictors of tourist expenditure and microeconomic modeling procedures used in their analysis. While two large sets of factors, i.e. economic and sociodemographic variables, have often been the subject of microeconomic modeling of tourist expenditures, variables which are related to the subject of expenditure have been taken into account insufficiently. The overview reveals the incompleteness of the tested models and in the literature the repeated recommendations to take into account the psychological variables which are missing in the models. The study describes the current state of defining and measuring psychological variables in tourism. Terms "psychographic variables" and "psychological characteristics of a tourist" are used for psychological variables in tourism research however, these were generally understood as respondents' current views on travel aspects, subjective evaluation of travel satisfaction, or as reasons for travel. As psychological variables in this study were considered the complex and relatively stable psychological characteristics of the person - personal values, personality and motivational system of the person as defined and measured in psychological science. Based on this, a conceptual model is developed which integrates economic, sociodemographic and psychological variables of expenditure and recommends procedures of its testing.
Keywords: Z32; 330; Tourist expenditures; economic model; psychological factors; conceptual models